Multinational companies and foreign direct investment in Algeria - Sellami, Amel (Journal of Human Sciences, 2023)
In recent years, countries' interest in attracting foreign direct investment by multinational companies has increased, given that multinational companies are the main driver of foreign direct investment at the global level. This type of investment has been able to have a significant impact on the economies of developing and developed countries alike, as these companies were able to penetrate many countries and establish projects under their control in oil and non-oil countries.Algeria, like the rest of the developing countries, has not stopped seeking to attract investment by multinational companies to what is happening in the economies of countries, so it has tried to achieve this based on creating its investment climate, trying to take advantage of the advantages of the latter as much as possible and achieve its development requirements.